Sea lamprey cardiac mitochondrial bioenergetics after exposure to TFM and its metabolites - Huerta, Belinda; Chung-Davidson, Yu-Wen; Bussy, Ugo; Zhang, Yizhu; Bazil, Jason N.; Li, Weiming (Aquatic Toxicology, 2020)
Population control of invasive sea lamprey relies heavily on lampricide treatment of infested streams. The lampricide 3-trifluoromethyl-4-nitrophenol (TFM) is thought to impair mitochondrial ATP production through uncoupling oxidative phosphorylation. However, the effect of TFM on the entire electron transport chain (complexes I to V) in the mitochondria is not clear. In addition, TFM is reduced in phase I metabolism by sea lamprey at higher levels than in other fish species. The effects of these TFM reductive metabolites on mitochondria have not been explored. In this study, we sought to examine the effects of TFM and its reductive metabolite amino-TFM (TFMa) on cardiac mitochondrial oxygen consumption and membrane potential to delineate potential mechanisms for toxicity. To determine if molecules with similar structure also exhibit similar effects on mitochondria, we used 4-nitro-3-methylphenol (NMP) and its reductive metabolites 4-amino-3-methylphenol (NMPa) and 4-nitroso-3-methylphenol (NMPn) for comparisons. We found that mitochondrial bioenergetics was heavily affected with increasing concentrations of TFM, NMP, and NMPa when complexes I and II of the electron transport chain were examined, indicating that the toxic action of these compounds was exerted not only by uncoupling complex V, but also affecting complexes I and II.
Keywords: Lampricides; Mitochondria toxicity; Reductive metabolism; Sea lamprey; dept.che; peer-reviewed